2014
DOI: 10.1097/sla.0b013e31829ccc5f
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Surgical Innovation

Abstract: Drawing on surgeons' own views is important for the development of a practical definition of surgical innovation. We have used a critical analysis of surgeons' own views as the basis for defining the core features of innovation. A precise definition of innovation will assist surgeons to identify and manage innovation and thereby enhance patient safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 12 publications
2
34
0
Order By: Relevance
“…IDEAL defines innovation as "a new or modified surgical procedure that differs from currently accepted local practice, the outcomes of which have not been described and which may entail risk to the patient" [4]. Critics claim this definition is overly broad [40], fails to distinguish between variation and research, and lacks practical utility [70]. Since correctly identifying when innovation is occurring is central to effective oversight, this is potentially a serious limitation [33].…”
Section: Introductionmentioning
confidence: 99%
“…IDEAL defines innovation as "a new or modified surgical procedure that differs from currently accepted local practice, the outcomes of which have not been described and which may entail risk to the patient" [4]. Critics claim this definition is overly broad [40], fails to distinguish between variation and research, and lacks practical utility [70]. Since correctly identifying when innovation is occurring is central to effective oversight, this is potentially a serious limitation [33].…”
Section: Introductionmentioning
confidence: 99%
“…6 The lack of clarity surrounding what constitutes surgical innovations makes them difficult to identify, particularly when they do not involve the purchase of new equipment or tools. 8 Currently, there is no gold standard for identifying innovation in surgery, which means hospitals may not have adequate processes for its management. 6 Identifying surgical innovation is central to ensuring its safety.…”
Section: Introductionmentioning
confidence: 99%
“…However, a recent study showing the results of interviews with 18 surgeons on what is innovation, showed that (the interviewed) surgeons hold no uniform view of surgical innovation, and that there is no agreement on the distinction between innovation and research. [19] …”
Section: Resultsmentioning
confidence: 99%
“…This difficulty defining surgical innovation was also observed when surgeons were asked to define and identify surgical innovation. [19] Clearly, some uniformity on what exactly is surgical innovation is a prerequisite when considering to launch surgical oversight committees. Otherwise it remains ambivalent which kinds of innovation should or should not be submitted for review.…”
Section: Discussion: Toward a Learning Health Care System?mentioning
confidence: 99%